Model-based Interpretation of the Performance and Degradation of Reformate Fueled Solid Oxide Fuel Cells - Kromp, Alexander (Schriften des Instituts für Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Werkstoffe der Elektrotechnik, 2013)
Solid oxide fuel cells offer great prospects for the sustainable, clean and safe conversion of various fuels into electrical energy. In this thesis, the performance-determining loss processes for the cell operation on reformate fuels are elucidated via electrochemical impedance spectroscopy. Model-based analyses reveal the electrochemical fuel oxidation mechanism, the coupling of fuel gas transport and reforming chemistry and the impact of fuel impurities on the degradation of each loss process.